If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (0) = -4.8x + 1.2 0 = -4.8x + 1.2 Reorder the terms: 0 = 1.2 + -4.8x Solving 0 = 1.2 + -4.8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.8x' to each side of the equation. 0 + 4.8x = 1.2 + -4.8x + 4.8x Remove the zero: 4.8x = 1.2 + -4.8x + 4.8x Combine like terms: -4.8x + 4.8x = 0.0 4.8x = 1.2 + 0.0 4.8x = 1.2 Divide each side by '4.8'. x = 0.25 Simplifying x = 0.25
| (2.5b-9)+6b=-7 | | 8m-6=2 | | 5(a-1)=5 | | 5(3x+-2)=4+-6x | | 4(3x+-2)=4+-6x | | -11=7+b | | 4w+10=90 | | 43v-6=8+23v | | 12x+6=5y+10 | | 4w+10= | | 2x-3(3-7)+3= | | 3(3x+-2)=4+-6x | | Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m | | 6m-2=m+3 | | (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 |